Potentials and Safety of Date Palm Fruit against Diabetes: A Critical Review - Mia, Md Al-Tareq (Foods, 2020)
Diabetes is a chronic metabolic disorder triggered by disturbances in carbohydrate, protein, and lipid metabolisms, where either reduced secretion or sensitivity of insulin is observed coupled with poor glucose control. Date palm fruits are one of the fruits reported to have good potential in diabetes treatment due to its presence of polyphenols exerting strong antioxidant activities. Other possible mechanisms of action include the polyphenolic compounds, which can inhibit enzymes like α-amylase and α-glucosidase. Flavonoids in dates can stimulate β-cells by increasing the number of islets and β-cells, recovering endocrine pancreatic tissues, reducing β-cell apoptosis, activating insulin receptors following the increase in insulin secretion, in addition to improving diabetes-induced complications. In this review, the in vitro, in vivo, and human study-based evidence of date palm as an anti-diabetic fruit is summarised.